NILAI PENDIDIKAN DALAM PERSPEKTIF AL-HADITS JIBRIL - Haerudin, Usep Malik; Inayah, Anidah (Globalwriting Academica Consulting & Publishing, 2022)
The purpose of this study is to analyze the value of education in the perspective of the hadith of Gabriel. This study uses a qualitative method with secondary data. The results of this study indicate that Islamic education in the perspective of Hadith Jibril includes an understanding of the basics of faith, sharia, Islamic laws and the nature of Ihsan. Because this religion includes these three things, as in the hadith of the story of Jibril when he asked the Prophet PBUH about Faith, Islam and Ihsan, the Prophet answered by giving the limitations. There the Prophet interpreted Iman with the six pillars of Faith (pillars of Iman), and interpreted Islam with its five pillars and gave an understanding of Ihsan by saying: